Purple Sweet Potato Reduces Malondialdehyde and TNF-a, Increases p53, and Protects Histopathological Appearance in Formaldehyde-induced Nasopharyngeal Carcinoma Rats - Ni Ketut Susilawati; I Wayan Putu Sutirta Yasa; Wayan Suardana; Sri Maliawan; I Made Jawi; Achmad Chusnu Romdhoni; Hamsu Kadriyan; I Wayan Gede Artawan Eka Putra; I Gusti Kamasan Nyoman Arijana (The Indonesian Biomedical Journal, 2022)
BACKGROUND:Purple sweet potato tuber ethanol extract (PSPTEE) has been known to have benefits in various disease, including to prevent nasopharyngeal carcinoma (NPC). However, there has been no research on PSPTEE in preventing the proliferation of nasopharyngeal mucosal epithelial cells induced by formaldehyde through the oxidative stress mechanisms and inflammatory process. Studies have proven the effect of PSP on various cancer cells, but the carcinogenesis process of the nasopharyngeal mucosal epithelium is still limited. Hence, this study aimed to demonstrate the mechanism for preventing histopathology changes with PSPTEE due to formaldehyde exposure.METHODS: Thirty-two formaldehyde-induced Wistar rats were treated with or without 1g/kgBW/day PSPTEE for 16 weeks. Malondialdehyde (MDA) level were examined with spectrophotometry method, while tumor necrosis factor (TNF)-α and p53 with enzyme linked immunosorbent assay (ELISA) method. The histopathology appearance of the nasopharyngeal epithelium was observed with hematoxylin-eosin (HE) staining.RESULTS: MDA and TNF-α levels in control and treatment group were 22.89±2.84 μM; 9.83±0.89 μM and 84.18±11.58 ng/L; 73.92±10.59 ng/L, respectively, and they showed significant difference. Meanwhile, the level of p53 showed no significant difference. Histopathology appearance showed a significant difference. Path analysis for MDA, TNF-α and p53 levels contributed 28.7% to histopathology appearance. MDA have an effect on significant direct effect on TNF-α. TNF-α has a significant direct effect to histopathological appearance. Indirect influence MDA on histopatological appearance were smaller than the direct effect. TNF-α has the greatest influence on histopatological appearance.CONCLUSION: Formaldehyde induces the histopathology appearance in nasopharyngeal epithelium. This study also demonstrates the mechanism to prevent the nasopharynx epithelial histopathology appearance by administration of PSPTEE.KEYWORDS: PSP, MDA, TNF-α, p53, nasopharynx epithelial